190 Timing of steroid doses and response rates to immune-checkpoint inhibitors in metastatic cancer. (9th November 2020) - Tawagi, Karine; Maslov, Diana; Simenson, Victoria; Yuan, Helen; Parent, Cameron; Bamnolker, Adi; Goel, Richa; Blake, Zoe; Madhav, KC; Matrana, Marc; Tawagi, Karine; Johnson, Daniel; et al.
Abstract : Background: Corticosteroids (CS) are the mainstay of immune-related adverse effect (irAE) management, as well as for other indications in cancer treatment. Previous studies evaluating whether CS affect immune checkpoint inhibitor (CPI) efficacy compared patients receiving steroids vs. no steroids. 1 This comparison may be confounded by different rates of irAEs, which are known to be associated with higher response rates to CPIs. Preclinically CS have been shown to diminish naïve T-cell proliferation and differentiation, 2 though there is a paucity of clinical data evaluating how the timing of concomitant CS affects CPI efficacy. Methods: We retrospectively collected data from patients treated with CPIs alone, who received CS during their CPI treatment at a single institution. Patients were allocated into two cohorts based on timing of initiation of CS (> 2 months vs. < 2 months after initiating CPI). Patient characteristics, irAEs, cancer type, treatment type, treatment response/progression per RECIST v1.1, and survival data were collected. Kaplan Meier and Cox proportional hazard regression methods were used to estimate hazard ratios (HR) for the primary endpoint of progression free survival (PFS) along with overall survival (OS). Results: We identified 247 patients with metastatic cancer who received CS concurrently with CPIs alone. The majority of patients had non-small cell lung cancer (n=98), followed by renal cell carcinoma (n=43), and melanoma (n=30). 242 patients were on PD-1 inhibitor monotherapy, while 45 patients received CPI in combination with anti-CTLA-4 ipilimumab (table 1). The median time on steroids for all patients was 1.8 months. After adjusting for differences in rates of treatment type, tumor type, brain metastases and irAEs, patients who were treated with CS > 2 months after starting CPI had a statistically significant longer progression free survival (PFS) [HR of 0.33, p≤0.0001], and overall survival (OS) [HR of 0.36, p≤0.0001] than those who received steroids < 2 months after starting CPI. Rates of irAEs in each group were not significantly different (p = 0.15). Objective response rate (ORR) for patients on CS > 2 months was 39.8%, vs. ORR for patients <2 months was 14.7% (p-value = <0.001). Conclusions: After adjusting for possible confounding factors such as rates of irAEs, our results suggest that early use of steroids during CPI treatment significantly hinders CPI efficacy. These data need to be validated prospectively. Future studies should focus on the immune mechanisms by which CS affect T-cell function early in CPI treatment course. References: Garant A, Guilbault C, Ekmekjian T, Greenwald Z, Murgoi P, & Vuong T. ( 2017). Concomitant use of corticosteroids and immune checkpoint inhibitors in patients with hematologic or solid neoplasms: a systematic review. Critical reviews in oncology/hematology 120, 86–92. Giles AJ, Hutchinson MKN, Sonnemann HM, Jung J, Fecci PE, Ratnam NM, . .. & Reid CM. Dexamethasone-induced immunosuppression: mechanisms and implications for immunotherapy. Journal for immunotherapy of cancer 2018;6(1):1–13.